Preliminary Genetic and Physiological Characterization of Starmerella magnoliae from Spontaneous Mead Fermentation in Patagonia - Kleinjan, Victoria (2025)
Honey possesses unique properties, characterized by its high sugar concentration and the synergistic interaction among nectar, pollen, bees, and yeasts. These features render it an exceptional substrate for exploring microbial diversity for bioprospecting purposes. In this study, we characterized fermentative yeast populations from 19 honey samples collected in Northern Patagonia, Argentina. A total of 380 yeast isolates were obtained, identifying eight yeast species. Starmerella magnoliae emerged as the dominant species, found in 76% of samples and representing 63% of total isolates. Intraspecific diversity analysis, using mtDNA-RFLP and sequencing of nuclear genes (FSY1 and FFZ1), revealed the presence of two distinct phylogeographic populations. Phenotypic assays indicated that most S. magnoliae strains tolerate high sulfite and ethanol concentrations, alongside exhibiting broad temperature tolerance, with some strains thriving even at 37 °C. Despite the fact that none of the strains completed the fermentation, microfermentation trials confirmed the fructophilic nature of this species and highlighted intraspecific variability in glycerol and acetic acid production. These findings underscore S. magnoliae as a promising non-Saccharomyces yeast for the fermented beverage industry.